2008
DOI: 10.1007/s10853-007-2411-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical testing of titanium/aluminium–silicon interfaces by push-out

Abstract: Abstract:Mechanical properties of Ti/Al-7Si assemblies produced by insert moulding have been studied with a classical push-out test and a variant that is the circular bending test. Special care has been taken for controlling both the reactivity at theTi/Al-7Si interface and the metallurgical health of the Al-7Si matrix. Mechanical tests until complete debonding have been completed with interrupted tests, metallographic characterizations and FEM analysis of elastic stress state. A mean shear strength of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…However, at 770°C, a thick interface with many shrinkage voids was observed. These voids were reported to exert detrimental effects on the mechanical characteristics of bimetallic joints [13]. Thus, the interfacial morphologies of Ti−6Al−4V/Al7050 joints strongly depended on the holding temperature in the first stage, and good interfacial metallurgical bonding can be possibly attained by parameter optimization, as shown in Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, at 770°C, a thick interface with many shrinkage voids was observed. These voids were reported to exert detrimental effects on the mechanical characteristics of bimetallic joints [13]. Thus, the interfacial morphologies of Ti−6Al−4V/Al7050 joints strongly depended on the holding temperature in the first stage, and good interfacial metallurgical bonding can be possibly attained by parameter optimization, as shown in Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Interface shear strength was measured using classical push-out tests, as described in Ref [13]. A universal testing machine was used to conduct push-out tests.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently demonstrated that an insert moulding of a titanium (Ti) rod in an Al-7Si-0.3Mg (in wt%) aluminium alloy can, when processed under appropriate conditions, lead to the formation of a strong metallurgical bond at the insert/alloy interface [1]. More precisely, a chemical reaction proceeds between the liquid aluminium alloy and the solid titanium insert, giving rise to the formation of a thin (less than 10 m thick) and continuous interface reaction layer.…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, a chemical reaction proceeds between the liquid aluminium alloy and the solid titanium insert, giving rise to the formation of a thin (less than 10 m thick) and continuous interface reaction layer. The mechanical properties of the resulting Ti/Al-7Si-0.3Mg joints, as evaluated by tensile testing [9] or pushout testing [1], have been shown to be higher than those of similar joints formed between cast iron inserts and an Al-7Si-0.3Mg alloy [9], or between mild steel inserts and an Al-13Si alloy [7]. Furthermore, it is well known that the mechanical properties of the magnesium-containing aluminium-silicon alloys can be enhanced by a heat treatment, of which the most widely used is the T6 treatment, made up of a solution treatment at 520-550 • C followed by quenching and artificial ageing [10].…”
Section: Introductionmentioning
confidence: 99%